Plant‐based diet index and erectile dysfunction in the Health Professionals Follow‐Up Study. (9th June 2022) - Yang, Heiko; Breyer, Benjamin N.; Rimm, Eric B.; Giovannucci, Edward; Loeb, Stacy; Kenfield, Stacey A.; Bauer, Scott R.
Abstract : Objective: To evaluate the longitudinal association between plant‐based diet index (PDI) score and incident erectile dysfunction (ED). Materials and Methods: We conducted a prospective analysis of 21 942 men aged 40 to 75 years who were enrolled in the Health Professionals Follow‐Up Study. ED was assessed with questionnaires every 4 years starting in 2000. Dietary data were collected via validated food frequency questionnaires completed every 4 years and were used to calculate total PDI scores, as well as healthy (hPDI) and unhealthy (uPDI) subscores. Multivariable Cox proportional hazards models were used to compute hazard ratios (HRs) for incident ED. All models were stratified by age (<60, 60 to <70, ≥70 years). Results: Among men aged 60 to <70 years, hPDI was inversely associated with incident ED. Those in the highest quintile of hPDI in that age group had an 18% lower risk of ED (HR 0.82, 95% confidence interval (CI) 0.73–0.91; P ‐trend <0.001) compared to those in the lowest quintile. Conversely, uPDI was positively associated with ED in men aged <60 years (HR 1.27, 95% CI 1.01–1.60; P ‐trend = 0.02). Conclusions: Encouraging a healthy plant‐based diet may be an environmentally sustainable intervention for men interested in maintaining erectile function.